The use of social semiotic multimodality and joint action theory to describe teaching practices: two cases studies with experienced teachers. Issue 3 (2nd July 2020) - Moro, Luciana; Mortimer, Eduardo F.; Tiberghien, Andrée
ABSTRACT: The aim of this study is to better understand how teachers use various embodied semiotic modes – speech, gestures, gaze, and proxemics – when they present scientific content to the entire class. To analyse the multimodal practices of these teachers, we integrated the social semiotic theory of multimodality and the joint action theory in didactics. We use a case study methodology to analyse the video data and to describe the productions of two teachers from selected short episodes. The results show several similar elements of these teachers' practices. In particular, their use of several coordinated modes to make a coherent meaning to complex aspects of scientific knowledge such as three- dimensional representations of chemical structures or the relation between an experiment and its model of light diffraction. Both teachers create signs by taking everyday things from their environment to re-signify them in a scientific way. Simultaneously they maintain contact with their students through their gaze and their position. In this way, they create or strengthen the classroom habits related to the explanation of knowledge.